2022
DOI: 10.3389/feduc.2022.969737
|View full text |Cite
|
Sign up to set email alerts
|

Exploring inclusive education in times of COVID-19: An international comparison of German, Austrian and Portuguese teachers

Abstract: With the start of the Coronavirus (COVID-19) pandemic, the global education system has a faced immense challenges and disruptions resulting in and the necessity for an immediate redesign of teaching and learning in the school context. Face-to-face classroom instruction had to be replaced by ‘emergency remote teaching’, requiring teacher to adapt their daily routines to a new and unprecedented educational reality. Researchers and policymakers worldwide have agreed that, despite the fact that efforts were made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 85 publications
0
7
0
1
Order By: Relevance
“…It is important to highlight that, in contrast to other countries in Europe such as Germany, Austria or Portugal (Contreras et al, 2022; Letzel‐Alt et al, 2022), Mexico did not reopen schools after the first COVID‐19 wave. In fact, it was decided that the school year starting in mid‐August 2020 would be implemented in the form of distance learning (Mexican Government, 2020).…”
Section: The Mexican Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…It is important to highlight that, in contrast to other countries in Europe such as Germany, Austria or Portugal (Contreras et al, 2022; Letzel‐Alt et al, 2022), Mexico did not reopen schools after the first COVID‐19 wave. In fact, it was decided that the school year starting in mid‐August 2020 would be implemented in the form of distance learning (Mexican Government, 2020).…”
Section: The Mexican Contextmentioning
confidence: 95%
“…Additionally, this study only considered certain variables (i.e., self‐efficacy) within its analyses. Nevertheless, international research has pointed out (Helm et al, 2021; Letzel et al, 2020; Letzel‐Alt et al, 2022), other key variables such as performance, (technological) resources, teachers' inclusive (online) practices, parental and teacher support, social interaction and digital competencies play an important role on students' emotional experiences. Consequently, further research is suggested to explore the interplay of such factors.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Enfin, la pandémie COVID-19, survenue peu après la mise en oeuvre de la LPS et la mise en discussion du Concept 360° auprès d'enseignant•e•s volontaires, a aussi pu complexifier les pratiques et particulièrement celles soutenant les élèves avec des BEP, comme la différenciation pédagogique (Letzel et al, 2020). L'étude comparative de Letzel-Alt et al (2022) a en effet montré qu'il avait été difficile pour les enseignant•e•s autrichien•ne•s et allemand•e•s de mettre en oeuvre des pratiques dites inclusives répondant aux besoins des élèves vulnérables et à haut risque, notamment durant le confinement. Ces tensions supplémentaires ont pu cristalliser davantage les attitudes à l'égard de la visée inclusive de l'école.…”
Section: Figure 3 Différences Significatives (Scores Z) Entre Les Deu...unclassified
“…For example, due to the different educational measures students from Croatia have spent less time in online education (8 weeks) compared with Serbia and Slovenia, where schools were fully closed for 28 and 21 weeks, respectively (Covid-19 Response, 2021). Given the differences in educational policies across countries during the pandemic, school support for children with ASN and parental involvement is also expected to differ significantly (Letzel-Alt et al, 2022). Therefore, our study examines the experiences of parents of children with ASN in the educational systems of Croatia, Serbia and Slovenia, which have similar educational and cultural traditions but had different-to a certain extent-educational measures during the pandemic.…”
Section: Context Of the Studymentioning
confidence: 99%